2018
DOI: 10.1029/2018gl078141
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Saturn's Nightside Plasma Sheet Using Cassini's Proximal Orbits

Abstract: Between April and the end of its mission on 15 September, Cassini executed a series of 22 very similar 6.5-day-period proximal orbits, covering the mid-latitude region of the nightside magnetosphere. These passes provided us with the opportunity to examine the variability of the nightside plasma sheet within this time scale for the first time. We use Cassini particle and magnetic field data to quantify the magnetospheric dynamics along these orbits, as reflected in the variability of certain relevant plasma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…A limitation of using a single mean ion mass along each individual field line is that the model cannot account for fine structural variation in magnetodisk thickness, caused by the concentration of heavier water ions towards the equatorial plane (e.g., Németh et al, ; Persoon et al, ) other limitations are discussed in detail in Achilleos, Guio and Arridge (). However, as demonstrated in that study, and Achilleos, Guio, Arridge, Sergis, et al () and Sergis et al (), the model can accurately reproduce global average trends observed in Saturn's magnetodisk. This model is therefore demonstrably adequate for reproducing the relatively large‐scale amplitude oscillations in the magnetic field data that are analyzed in this study.…”
Section: Methodssupporting
confidence: 61%
“…A limitation of using a single mean ion mass along each individual field line is that the model cannot account for fine structural variation in magnetodisk thickness, caused by the concentration of heavier water ions towards the equatorial plane (e.g., Németh et al, ; Persoon et al, ) other limitations are discussed in detail in Achilleos, Guio and Arridge (). However, as demonstrated in that study, and Achilleos, Guio, Arridge, Sergis, et al () and Sergis et al (), the model can accurately reproduce global average trends observed in Saturn's magnetodisk. This model is therefore demonstrably adequate for reproducing the relatively large‐scale amplitude oscillations in the magnetic field data that are analyzed in this study.…”
Section: Methodssupporting
confidence: 61%
“…The hot plasma (>3 keV) is well sampled by the Magnetospheric Imaging Instrument (MIMI, Krimigis et al, 2004) cluster of instruments. MIMI instrument measurements have been used to characterize the hot plasma and its moments in Saturn's magnetosphere (e.g., Dialynas et al, 2017;Dialynas et al, 2018;Kane et al, 2014Kane et al, , 2008Sergis et al, 2018Sergis et al, , 2017Sergis et al, , 2010Sergis et al, , 2009Sergis et al, , 2007. Two of the three MIMI instruments, the Ion and Neutral Camera (INCA) and the Charge Energy Mass Spectrometer (CHEMS) provided the data analyzed here.…”
Section: Introductionmentioning
confidence: 99%
“…This mitigates our sensitivity to the high‐latitude loci of the field lines predicted by our models. In addition, similar mappings of UCL/AGA model calculations have been used in Sergis et al () to confirm that hot plasma pressure is approximately uniform along magnetic field lines, using high‐latitude proximal Cassini orbits.…”
Section: Resultsmentioning
confidence: 68%